2008
DOI: 10.1152/ajpgi.00130.2007
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of intramuscular ICC increases fundic muscle excitability but does not impede nitrergic innervation

Abstract: The motility of the gastrointestinal tract is generated by smooth muscle cells and is controlled to a large extent by an intrinsic neural network. A gap of ∼200 nm usually separates nerve varicosities from smooth muscle cells, which suggests that direct innervation of the smooth muscle by synapses does not occur. Enteric nerves do make synapse-like contact with proposed regulatory cells, the interstitial cells of Cajal (ICC), which in turn may be in gap junction contact with smooth muscle cells. The role playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…Whether the purinergic ATPdependent fIJP is regulated via ICC remains an outstanding question, which has to be addressed by conditional loss-offunction experiments in the future. Data from W/W v mice indicate that the purinergic fIJP potential is not altered by the loss of ICC subpopulations 41 .…”
Section: Discussionmentioning
confidence: 94%
“…Whether the purinergic ATPdependent fIJP is regulated via ICC remains an outstanding question, which has to be addressed by conditional loss-offunction experiments in the future. Data from W/W v mice indicate that the purinergic fIJP potential is not altered by the loss of ICC subpopulations 41 .…”
Section: Discussionmentioning
confidence: 94%
“…Our findings suggest the possibility that reports of retained nitrergic responsiveness in Kit mutants may have included animals with only partial lesions in the ICC population. 14,15,17,25 Since the first experiments in which Kit mutants were used for functional studies of ICC, it was recognized that loss of ICC is incomplete in W/W V mice. 1 For example, ICC-MY are largely lost in the small intestine, but ICC-DMP (the equivalent of ICC-IM in the small bowel) are not reduced greatly in numbers.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] However, there is considerably more controversy regarding the role of ICC as mediators of enteric motor neurotransmission. Several publications have argued against the role of ICC as intermediaries in motor neurotransmission and suggested that changes in smooth muscle cells (SMCs) or other factors can account for differences in neural responses between wild-type animals and mutants in which ICC-IM are reduced (e.g., W/W V and Sl/Sl d mice and Ws/Ws rats [14][15][16][17] ). More recently, using a cell specific Cre-loxP approach, it was concluded that both ICC-IM and smooth muscle are involved in enteric nitrergic neural responses in the fundus.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that ICC-IM are not involved in nitrergic [222][223][224][225] or cholinergic neurotransmission. 222 229 These data support the hypothesis that ICC-IM mediate nitrergic inhibitory neurotransmission in the fundus and may explain the discrepancies in previous functional studies.…”
Section: Evidence Opposing a Role For Interstitial Cells Of Cajal In mentioning
confidence: 99%